Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Canopus Konverta Industri - Dimas Hibatullah Habibi; Muhamad Azis Firdaus; Syahrum Agung (Indonesian Journal of Innovation Multidisipliner Research, 2023)
This study aims to determine how much influence the variables of compensation and work discipline have on employee performance. This research was conducted by distributing questionnaires to 42 employees of PT. Canopus Konverta Industry in Sukahati Bogor Regency, processed with the Smart PLS 4.0 application with the SEM (structural equation modeling) analysis method. The results obtained from the effect of compensation on employee performance: significance with P values = 0.008 less than 0.05 with a hypothesis T value of 2.664 greater than 1.96 and (O = 0.292) means that there is a significant influence between compensation variables on employee performance. Work discipline on employee performance: significance with a value (O) = 0.675 and significant, with a P value = 0.000 less than 0.05, and a calculated T value of 6.223 greater than 1.96, which means that there is a significant influence between work discipline variables on employee performance. The results obtained from the effect of the compensation variable on work discipline: significance with a P value = 0.000 less than 0.05, with a hypothesis T value of 11.752 greater than 1.96 and (O = 0.900), meaning that there is a significant influence between the compensation variables on work discipline variables. The results of the analysis of the compensation path through work discipline on employee performance: significance with a value where the calculated T value is 5.472 greater than 1.96, with a P value of 0.000 less than 0.05, and a value (O = 0.608), meaning that it shows the strength of influence and the nature of the relationship of exogenous to endogenous variables through work discipline are stated to be moderate.